Analysis of the indicators of the educational process and scientific levelUsing the analysis of variance of ordered data in repeated measurements - خلف كمال علوان; محمد لقاء علي (Journal of Economics and Administrative Sciences, 2011)
In this research want to make analysis for some indicators and it’s classifications that related with the teaching process and the scientific level for graduate studies in the university by using analysis of variance for ranked data for repeated measurements instead of the ordinary analysis of variance . We reach many conclusions for the important classifications for each indicator that has affected on the teaching process.